Facile regioselective decomposition of tosylhydrazones: an application towards the synthesis of alpha-lipoic acid - Chavan, Subhash P.; Kale, R. R.; Pasupathy, K. (Synlett, 2005)
A facile regioselective decomposition of tosylhydrazones using NaOH as a base in refluxing isopropyl alcohol is described. This finding has been Successfully applied towards the synthesis of (&PLUSMN;)-α-lipoic acid (1).
Keywords: alpha-lipoic acid; Olefins; Regioselectivity; tosylhydrazones

Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone